THE THE IMPORTANCE OF STUDENTS’ SELF EFFICACY AWARNESS IN LEARNING ENGLISH - Suryanovika, Citra (Jurnal Ilmiah Spectral, 2017)
This article reviews the importance of self-efficacy in learning English and some ways to promote self-efficacy. Recently, self-efficacybecomes a well-known subject in learning and teaching English as a foreign language. Some former researches have shown the positive impact of self-efficacy on academic performance, defined as a self-oriented perception in assessing his/her capability in learning English. Teachers may encourage students to enhance their self-efficacy through some approaches. They may employ student-centered learning, accommodate students’ learning styles through varied teaching strategies and approaches, provide clear instruction, routine practice and feedbacks.